Synthesis, characterization and catalytic studies of barium exchanged ETS-10 in knoevenagel condensation reaction - Noor Hazzarita Abdullah, 1989-; Mustaffa Shamsuddin, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2010